Pengaruh Media Pembelajaran Kartu Bergambar (Flash card) Terhadap Hasil Belajar Biologi Siswa Kelas X IPA MA Dakwah Islamiyah Putri Kediri Lombok Barat - Sarnia, Saza; Japa, Lalu; Artayasa, I Putu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to analyze the influence of flash card learning media on the biology learning outcomes of class X students at MA Dakwah Islamiyah Putri Kediri, West Lombok. This type of research is experimental research. The population in this research is class X Science students at MA Dakwah Islamiyah Putri Kediri West Lombok, totaling 234 students. The research sample was selected using a purposive sampling technique and obtained class X IPA 2 as the experimental class which was treated with picture card media (Flash cards) and Student learning results show that the average score of experimental class students who were given flash card media treatment was higher compared to the control class who did not use learning media. The results of the hypothesis test also show the Sig value. smaller than 0.05, which means that the use of picture card learning media (Flash cards) has a real influence on the ranking of students' learning outcomes in class X Science MA Dakwah Islamiyah Putri Kediri West Lombok.